2011
DOI: 10.2337/db11-0007
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Plasminogen Activator Inhibitor-1 Restores Skeletal Muscle Regeneration in Untreated Type 1 Diabetic Mice

Abstract: OBJECTIVEType 1 diabetes leads to impairments in growth, function, and regenerative capacity of skeletal muscle; however, the underlying mechanisms have not been clearly defined.RESEARCH DESIGN AND METHODSWith the use of Ins2WT/C96Y mice (model of adolescent-onset type 1 diabetes), muscle regeneration was characterized in terms of muscle mass, myofiber size (cross-sectional area), and protein expression. Blood plasma was analyzed for glucose, nonesterified fatty acids, insulin, and plasminogen activator inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
80
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 47 publications
9
80
1
Order By: Relevance
“…Tiplaxtinin (PAI-039), the most well studied small-molecule inhibitor, attenuates asthmatic episodes, reduces both hyperlipidemia and hyperglycemia, suppresses angiogenesis and has recently been identified as a potent inhibitor of carotid stenosis by stimulating vascular smooth muscle cell apoptosis [13][14][15][16][17][18][19][20]. Similarly, other compounds that share a similar binding site on PAI-1 as tiplaxtinin have been synthesized [21,22].…”
Section: Structure and Chemical Antagonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tiplaxtinin (PAI-039), the most well studied small-molecule inhibitor, attenuates asthmatic episodes, reduces both hyperlipidemia and hyperglycemia, suppresses angiogenesis and has recently been identified as a potent inhibitor of carotid stenosis by stimulating vascular smooth muscle cell apoptosis [13][14][15][16][17][18][19][20]. Similarly, other compounds that share a similar binding site on PAI-1 as tiplaxtinin have been synthesized [21,22].…”
Section: Structure and Chemical Antagonistsmentioning
confidence: 99%
“…Since it is known that tiplaxtinin and TM5275 promote PAI-1 substrate behavior, however, these inhibitors may prevent the conformational change in β-sheet A of PAI-1 necessary to accommodate insertion of the PAI-1 RCL during the protease inhibition reaction [25]. If tiplaxtinin or TM5275 were to complex with PAI-1 at the vitronectin-binding site, it has been suggested that these inhibitors would not be effective since the majority of circulating PAI-1 is bound to vitronectin; nevertheless, the available data confirm significant in vivo efficacy for these drugs [13][14][15][16][17][18][19][20]27]. Figure 1.…”
Section: Structure and Chemical Antagonistsmentioning
confidence: 99%
“…Moreover, we recently demonstrated in female mice with streptozotocin-induced type 1 diabetes that PAI-1 is involved in bone loss (16). PAI-1 is upregulated in atrophic skeletal muscle (17), and this change is associated with impaired muscle regeneration (18,19). Several clinical studies showed that circulating PAI-1 concentration is elevated in patients with Cushing syndrome or during corticosteroid treatment (20,21).…”
mentioning
confidence: 99%
“…Surprisingly, a limited number of studies have investigated the effects of regular physical activity on skeletal muscle growth and development in rodent models of adolescent diabetes. Indeed, much of what we know about diabetic myopathy has been from studies published on rodents living in sedentary cage conditions [3,[8][9][10]. Studies employing resistance type exercise in Px rats [16,17] or via non-physiological ablation of the gastrocnemius to overload the soleus and plantaris muscles in rat models of diabetes [30] show that resistance exercise fails to increase protein synthesis during severe hypoinsulinaemia/hyperglycaemia.…”
Section: Discussionmentioning
confidence: 99%
“…The partially pancreatectomised (Px) rat is one model of choice, as it mimics hypoinsulinaemia/hyperglycaemia, with some basal insulin production, which is similar to a child with diabetes at the time of diabetes diagnosis or a child who is receiving inadequate insulin administration. Poor glycaemic control in young rodent models of diabetes is associated with reduced muscle growth, function and repair, at least in sedentary cage conditions [3,[8][9][10]. Impairments in growth occur particularly in the type II/ glycolytic fibres, in part because of decreased rates of muscle protein synthesis [11][12][13] and probably through a reduced capacity of mammalian target of rapamycin complex 1 (mTORC1) signalling in response to protein intake [9].…”
Section: Introductionmentioning
confidence: 99%